Vegetative and reproductive morphological aspects of Dermonema (Rhodophyceae: Liagoraceae) in Mexico - Pedroche, Francisco F.; Avila Ortiz, Alejandrina (Instituto de Ecología, A.C., 1996)
Morphological and reproductive features of the genus Dermonema from the tropical Pacific coast of Mexico are reviewed in this report. The chief ones are: thallus construction, in which lax cells integrate well defined cortical, subcortical, and medullar zones; spermatangial branches arising from subapical cells; carpogonial branches having a lateral origin; gonimoblasts being composed of diffuse sympodial filaments in which terminal cells are transformed directly into carpospores. The tetrasporangial phase was not observed. This genus shows preference for warm waters and is distributed in Mexico from Isla Ildefonso in the Gulf of California to Puerto Angel, Oaxaca. The plants live in the upper intertidal splashing zone with strong wave action and are vigorous between April and September. The type material of Nemalion virens J. Agardh was examined and found to be conspecific with the alga previously known as Dermonema frappieri (Montagne et Millardet) Boergesen. Consequently the new nomenclatural combination Dermonema virens (J. Agardh) Pedroche et Avila Ortiz, is established.